2014
DOI: 10.1038/nn.3904
|View full text |Cite
|
Sign up to set email alerts
|

Theta sequences are essential for internally generated hippocampal firing fields

Abstract: Sensory cue inputs and memory-related internal brain activities govern the firing of hippocampal neurons, but which specific firing patterns are induced by either of the two processes remains unclear. We found that sensory cues guided the firing of neurons in rats on a timescale of seconds and supported the formation of spatial firing fields. Independently of the sensory inputs, the memory-related network activity coordinated the firing of neurons not only on a second-long timescale, but also on a millisecond-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
313
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(361 citation statements)
references
References 58 publications
36
313
3
Order By: Relevance
“…This difference between temporal and spatial representation may be attributable to absence of temporal cues beyond the onset of running in contrast to the prevalence of spatial cues throughout traversal of the maze. This account is consistent with reports that, when environmental cues are reduced, spatial information in place cell activity is diminished (Wang et al, 2015). Increasing field width and decreasing representation over time is a central feature of temporal coding that enables increased efficiency when encoding in a scale invariant manner (Howard et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This difference between temporal and spatial representation may be attributable to absence of temporal cues beyond the onset of running in contrast to the prevalence of spatial cues throughout traversal of the maze. This account is consistent with reports that, when environmental cues are reduced, spatial information in place cell activity is diminished (Wang et al, 2015). Increasing field width and decreasing representation over time is a central feature of temporal coding that enables increased efficiency when encoding in a scale invariant manner (Howard et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…This difference in the organization of network coding of time and space is paralleled by a recent observation that, whereas hippocampal time cell representations depend on the theta rhythm, place cell representations do not (Wang et al, 2015). Thus, although time and space coding are very similar in many ways described here, the circuit mechanisms and consequent organization of network representation may be distinct and adaptive to differing demands for internal information processing in the time domain as contrasted with external information processing in the spatial domain.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our results demonstrate the modulatory effects of increased neuronal slow oscillations on corticocortical and hippocampal-cortical connectivity. Numerous studies have demonstrated the importance of hippocampal and cortical theta oscillations (4-12 Hz) (60) to coordinate groups of neurons to integrate sensory information (61) and consolidate memory (62,63). Comparatively, our results suggest that the hippocampus plays an even greater role in coordinating brain-wide neural activity, particularly at slow oscillations.…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, CA1 sequential activity is also observed during the delay period of tasks such as the DNTP procedure described earlier; that is, tasks in which rats must alternate between taking different spatial routes on successive trials (Pastalkova et al 2008;Gill et al 2011;Kraus et al 2013,). In a spatial alternation task, it was recently reported that time-cell sequences in the CA1 are profoundly disrupted by temporary inactivation of the medial septum during the delay period and performance was also impaired (Wang et al 2015). Because the medial septum sends diverse and diffuse projections to the HPC and EC (Meibach and Siegel 1977), future work will be needed to tease apart the precise mechanisms at the heart of this disruption.…”
Section: The Hippocampal Ca1 Area Supports Temporal Associative Learningmentioning
confidence: 88%